The Effectiveness of Group Counseling With Stress Inoculation Training to Improve Students Self-Esteem - Diyah Palupi, Elvia Purwaningrum; Sunawan, Sunawan; Murtadho, Ali (Jurnal Bimbingan Konseling, 2020)
Students with low self-esteem tend to be unconfident about enrolling at public university realized by the feeling of pessimism and failure. In relation to this, the current study attempted to examine the effectiveness of group counseling with stress inoculation training to improve students’ self-esteem. It used experimental method with pretest-posttest design. There were 14 ninth grade students involved as the subject of this study chosen using purposive sampling. After their data were analyzed, it was found that group counseling with stress inoculation training technique was effective to improve students’ self-esteem. These findings proved the effectiveness of group counseling with stress inoculation training technique to improve students’ self-esteem in public university enrolment